Quality of raw milk in the highland tropics of Nariño, Colombia = Calidad de la leche cruda en el trópico alto de Nariño, Colombia - Tobar Delgado, Magaly Elizabeth
Introduction. The production and commercialization of raw milk in Nariño, Colombia, follows microbiological and compositional standards on which payment for quality is made. However, quality can be affected during its transport after milking. Objective. To describe the microbiological and compositional quality of raw milk in the highland tropic. Materials and methods. The study was carried out in seven municipalities in the department of Nariño, Colombia, during the rainy season between February and July of 2017. Two milk samples from the same milk can were collected, one after milking (farm; n = 10), and the second at the collection point (tank; n = 10). In each sample, the following variables were evaluated: height above the sea level of the collection site, aerobic mesophilic count (CFU), total coliform count (COL), milk temperature, fat (FAT), protein (PC) and total solids (TS). Results. The temperature of the milk was higher on the farm compared to the tank (30±0.68 vs. 23±0.87 °C, respectively). The aerobic mesophilic count was higher in the tank vs. farm (116,470 vs. 41,388 CFU ml-1, respectively). The temperature of the milk was negatively correlated with the distance and the transport time of the milk (-0.86 and -0.84, respectively). The compositional quality of the milk was not affected by transport conditions. Conclusion. In the high tropic conditions, the microbiological quality of raw milk was negatively affected by the increase in the aerobic mesophilic counts.